Time to Initiation of Clozapine Treatment in Children and Adolescents with Early-Onset Schizophrenia - Trinczek, E.; Heinzel-Gutenbrunner, M.; Haberhausen, M.; Bachmann, C. J. (Pharmacopsychiatry, 2016)
Introduction: Early-onset schizophrenia (EOS) has a poor prognosis and is difficult to treat, which often leads to the initiation of clozapine treatment. Studies in adults have shown that the initiation of clozapine treatment is often delayed. There is a lack of studies concerning the initiation of clozapine in children and adolescents with EOS. The aim of this study was to investigate the time span from first EOS-related psychiatric hospitalization to clozapine initiation.Methods: We retrospectively studied a consecutive cohort of children and adolescents with EOS and first-time clozapine prescriptions from a tertiary care child and adolescent psychiatric center in Germany.Results: Clinical records with data on clozapine initiation were available for 112 patients (35.7% females, mean age: 15.2±1.6 years). The mean time from first EOS-related hospitalization to clozapine initiation was 1.1 (±1.0) years, with an average of 2.3 (±1.1) prior antipsychotic treatment episodes. Higher age and higher IQ predicted earlier clozapine initiation. At the time of clozapine initiation, 40.2% of patients received antipsychotic polypharmacy. Prior to clozapine, 33.9% of patients had received 3 or more antipsychotic treatment episodes.Discussion: In our study, clozapine treatment was initiated markedly earlier than in the few existing studies, which may partly be due to the expected poor prognosis of EOS. The significant portion of patients undergoing 3 or more antipsychotic trials or antipsychotic polypharmacy prior to clozapine may indicate a need for improved dissemination of knowledge on the effectiveness of clozapine in treatment-resistant schizophrenia in order to promote timely clozapine prescriptions in these cases.
Keywords: adolescents; children; clozapine; Germany; polypharmacy; early-onset schizophrenia